The Nursing care services rendered to patients in Primary Health Care Centers in Anambra and Lagos States in fulfillment of SDGs 3.8 - Henrietta. A. RN, Okedo (International Journal For Research In Health Sciences And Nursing, 2024)
Globally, there is the call for improvement of the primary health care system, which is by nature, community-based and stands as the closest to the people. The primary health care system was designed to be efficient, accessible, affordable, collaborative and interdependent in order to face the dynamics of emerging and reemerging diseases, as well, as the chronic health issues such as heart disease, diabetes, cancer and mental health challenges that are constantly plaguing a significant number of people across the globe. This study sought to highlight the various (numerous) nursing care services rendered to the clients/patients at the primary healthcare level. A non-experimental descriptive cross-sectional design was adopted in the study to assess nursing care services rendered to patients/clients in 18 selected primary health care facilities in Anambra and Lagos States. The research instrument was structured questionnaire . The data obtained from the study were collated, tallied and analyzed using statistical software package for social sciences (SPSS, Version 20). Findings from the study indicated that almost 80% of the services provided in the facilities were rendered by nurses/midwives. In conclusion, achievement of SDG. 3.8 will not be possible without the nurses and midwives.